Complication-Effectiveness Analysis for Unruptured Intracranial Aneurysm Surgery: A Prospective Cohort Study. Issue 5 (9th November 2015) - Morgan, Michael Kerin; Wiedmann, Markus; Assaad, Nazih N.; Heller, Gillian Z.
Abstract: BACKGROUND: The aim of intervention for unruptured intracranial aneurysms (UIAs) is safe, effective treatment. OBJECTIVE: To analyze a prospective database for variables influencing the risk of surgery to produce a risk model adjusting this risk for effectively treated aneurysms. METHODS: First, we identified variables to create a model from multiple logistic regression for complications of surgery leading to a 12-month modified Rankin Scale score >1. Second, we established the long-term cumulative incidence of freedom from retreatment or rupture (treated aneurysm) from Kaplan-Meier analysis. Third, we combined these analyses to establish a model of risk of surgery per effective treatment. RESULTS: One thousand twelve patients with 1440 UIA underwent 1080 craniotomies. We found that 10.1% (95% confidence interval [CI], 8.4-12.0) of craniotomies resulted in a complication leading to a modified Rankin Scale score >1 at 12 months. Logistic regression found age (odds ratio, 1.04; 95% CI, 1.02-1.06), size (odds ratio, 1.12; 95% CI, 1.09-1.15), and posterior circulation location (odds ratio, 2.95; 95% CI, 1.82-4.78) to be significant. Cumulative 10-year risk of retreatment or rupture was 3.0% (95% CI, 1.3-7.0). The complication-effectiveness model was derived by dividing the complication risk by the 10-year cumulative freedom from retreatment or rupture proportion. Risk per effective treatment ranged from 1% for a 5-mm anterior circulation UIA in a 20-year-old patient to 70% for a giant posterior circulation UIA in a 70-year-old patient. CONCLUSION: Complication-effectiveness analyses increase the information available with regard to outcome for the management of UIAs.